1992
DOI: 10.1111/j.1365-3059.1992.tb02559.x
|View full text |Cite
|
Sign up to set email alerts
|

A new yellowing disease of cucurbits caused by a luteovirus, cucurbit aphid‐borne yellows virus

Abstract: Since 1988, a yellowing disease of melon, cucumber and zucchini squash has been frequently observed in summer and autumn crops in France. Infected plants show yellowing and thickening of the older leaves; symptom intensity differs depending upon cultivar and season, and can be easily overlooked when plants are already infected by mosaic‐inducing viruses or other pathogens. The disease is associated with the presence of a virus with spherical particles c. 25 nm in diameter, which is readily transmitted in a per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
119
1
9

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(131 citation statements)
references
References 18 publications
(26 reference statements)
1
119
1
9
Order By: Relevance
“…4B, lane 3). Note that the difference in silencing suppressor activity of the different P0s does not correlate with compatibility between the virus and the host used in the patch coinfiltration assay, since PLRV, like BWYV, infects N. benthamiana, whereas CABYV does not (19).…”
Section: Resultsmentioning
confidence: 99%
“…4B, lane 3). Note that the difference in silencing suppressor activity of the different P0s does not correlate with compatibility between the virus and the host used in the patch coinfiltration assay, since PLRV, like BWYV, infects N. benthamiana, whereas CABYV does not (19).…”
Section: Resultsmentioning
confidence: 99%
“…This plant was found to be devoid of other mosaicinducing viruses by double antibody sandwich (DAS) ELISA and by electron microscope examination, but it was infected by cucurbit aphid-borne yellows luteovirus (CABYV). Since CABYV is not sap transmissible (Lecoq et al, 1992), this contaminant was easily eliminated by mechanical inoculation to C. pepo. The ZYMV isolate was subjected to three successive single local lesion transfers in Chenopodium amaranticolor and Chenopodium quinoa before being maintained in C. pepo or kept dried over calcium chloride.…”
Section: Virus Isolate and Host Range Studymentioning
confidence: 99%
“…In cucurbits, the only polerovirus known for a long time was Cucurbit aphid-borne yellows virus (CABYV; Lecoq et al, 1992). However, molecular studies have revealed that at least six different species infect this plant family: CABYV which is present worldwide, four species (Cucumber aphid-borne yellows -Hainan virus, Luffa aphid-borne yellows virus, Melon aphid-borne yellows virus and Suakwa aphid-borne yellows virus) found only in Asia, and Pepo aphidborne yellows virus (PABYV) first observed in 2008 in Mali (Knierim et al, 2014), and more recently in South Africa (Ibaba et al, 2015), Côte d'Ivoire (Kone et al, 2015) and Greece (Lotos et al, 2016 Total RNA was extracted from infected tissues using the TRI-reagent, and RT-PCR was performed with polerovirus primers Pol-G-F and Pol-G-R (Knierim et al, 2014).…”
mentioning
confidence: 99%